Asymmetric property rights in China's economic growth - Zhang, Xiaobo (International Food Policy Research Institute, 2006)
This paper highlights the difference between secure investor property rights and loosely defined individual property rights. Globalization and fiscal decentralization have intensified this difference. On the one hand, in the presence of mobile foreign direct investments and under the arrangement of fiscal decentralization, local governments compete vigorously to offer various protections on the property rights of investors; on the other hand, local governments and developers attempt to acquire land at as low price as possible by taking advantage of the loopholes inherent in the Chinese law. Secure investor property rights together with weak protections on individuals’ land property rights is argued to be one of the major drivers of China’s rapid economic growth. But the same factor can veer those individuals being deprived of land into violence and social unrest, which may undermine China’s social stability and long-term sustainable growth.